[OP.7A.06] TREATING HYPERTENSIVE CRISES BETWEEN GUIDELINES AND REAL-WORLD: AN ANTI-HYPERTENSIVE ROLE OF ANTI-ANXIETY DRUGS?. (September 2016) - Gabba, M.; Salinaro, F.; Mussinelli, R.; Boldrini, M.; Raimondi, A.; Belotti, C.; Maggi, A.; Perrone, T.; Bressan, M.A.; Perlini, S.
Abstract : Objective: Current ESH Guidelines are extensively devoted to diagnosis, management and follow-up of arterial hypertension in the "chronic" setting, whereas less attention is given to the acute management of hypertensive crises, a group of potentially life-threatening complications. Moreover, epidemiological data concerning hypertensive crises are limited. Design and method: During 2014, 457 consecutive patients with an initial systolic blood pressure (SBP) >170 mmHg and/or diastolic blood pressure (DBP) >110 mmHg were enrolled after being admitted to an Emergency Department (ED) serving a population of more than 50000 inhabitants, Results: Hypertensive crises represented 0.95% of the total number of ED admissions (n = 48054). Hypertensive emergencies (i.e. hypertensive crises associated with organ damage), were 113/457 (25%), the remaining 344/457 (75%) being hypertensive urgencies. Global mortality rate was 0.87%, (4% in the subset of hypertensive emergencies). Female patients were the majority in both hypertensive urgencies (65.1%) and emergencies (53.1%). Mean age was 68.5 years (range: 23–97). The presence of hypertension (either treated or untreated) was already known in 67.1% of cases. Treatment was associated with significant blood pressure reduction in both urgencies (SBP = −42.1 mmHg, DBP = −19.4 mmHg) and emergencies (SBP = −40.5 mmHg, DBP = −21 mmHg; p < 0.001 for both) in a relatively short time span (<5 hours). As expected, acute treatment of hypertensive emergencies was based on a combination of diuretics, nitrates, labetalol and urapidil. In contrast, in hypertensive urgencies the most commonly prescribed drugs were clonidine (44.3%) and diazepam (36.3%). Although not recognized as an antihypertensive drug, diazepam is widely used in the management of hypertensive crises. Notably, diazepam-treated patients achieved a similar extent of blood pressure reduction when compared with patients not receiving antianxiety treatment. Moreover, diazepam administration was associated with a faster reduction in blood pressure and a significantly lower number of associated anti-hypertensive drugs (0.7 vs 1.2; p < 0.01). During a 11-month follow-up, re-admissions caused by hypertensive crises were 63 (13.8%), without any difference related to diazepam treatment. Conclusions: Anti-anxiety drugs are commonly used in hypertensive crises, showing an interesting role in "real-world" treatment. Further studies are warranted to better define their role as "anti-hypertensive" drugs.